Withdrawing Assisted Nutrition in Neonates: A Survey on Attitudes and Insights in Argentina - Mariani, Gonzalo L.; Konikoff, Laura L. (American Journal of Perinatology, 2023)
Objective This study aimed to assess beliefs and attitudes of Argentinean neonatologists and neonatal nurses regarding end-of-life care of newborn infants, including withdrawal of clinically assisted nutrition and hydration (CANH).Study Design A five-domain survey was sent to 465 neonatal health care workers, which included demographic data, general ethical concepts, participation in end-of-life decisions, beliefs about end-of-life care practices, and presentation of four clinical scenarios. Standard statistical tests were used, and a multivariable analysis was done to evaluate variables independently associated with rejecting the withdrawal of CANH.Results A total of 227 questionnaires were anonymously completed, 60% by physicians and 40% by nurses. More respondents agreed to withdraw mechanical ventilation in comparison to CANH in patients under certain circumstances (88 vs. 62%, p < 0.01). The most accepted variables when deciding to withdraw care were the quality of life perceived by parents (86%) and their religious beliefs (73%). A total of 93% agreed that parents should be included in the decision, but only 74% acknowledged they are included in real practice. Considering the scenario of a newborn with severe and irreversible neurological compromise, 46% of respondents were opposed to suspending enteral nutrition. No independent variables were found to be associated with opposing the withdrawal of CANH. Of those agreeing to withdraw enteral feeds under certain circumstances, for the severely neurologically affected neonate 58% would either refuse to limit enteral feeds or consult with an ethics committee before doing so. When given the scenario of their own severe and irreversible neurological compromise, 68% agreed to have enteral feeds withdrawn to themselves, and they were more likely to agree with withdrawing feeds for the severely compromised neonate (odds ratio: 7.2; 95% confidence interval: 2.7–24.1).Conclusion While most health care providers agreed to withdraw life-sustaining support under certain conditions, many were reluctant to suspend CANH. Many responses differed when being asked as general statements versus actual clinical scenarios.Key Points
Keywords: health care providers attitudes; neonates; life support care/ethics; withdrawing treatment